2a = 24 + 12a
-10a = 24
a = -12/5
2006-11-10 09:45:15
·
answer #1
·
answered by bourqueno77 4
·
2⤊
2⤋
2A = 3 (8 + 4A) Multiply by 3 on both sides. Cancel out 3 at left side.
2A = 24 + 12A Distribute 3.
2A/2 = (24 + 12A)/2 Divide by 2 on both sides.
A = 12 + 6 Cancel 2 at left side. Divide 24 and 12 by 2 on right side.
A - 6A = 12
-5A = 12
A = 12/-5
A = -2 2/5
2006-11-10 18:00:03
·
answer #2
·
answered by emily 3
·
0⤊
3⤋
First multiply by 3 to get 2A = 24 + 12A. Then you simplify to (2A - 12A) = 24 which then equals -10A=24 and then A=24/(-10) = -2.4 and so solving the equation: A = - 2.4
2006-11-10 17:53:18
·
answer #3
·
answered by Tom Heston 2
·
2⤊
0⤋
2A/3=8 + 4A => subtract 4A from both sides
2A/3 - 4A = 8 =>
2A/3 - 12A/3 = 8 =>
-10A/3 = 8 =>
-10A = 24 =>
A = -2.4
2006-11-10 17:49:38
·
answer #4
·
answered by Anonymous
·
3⤊
0⤋
To get rid of the three in 2A/3, multiply each side by three: 2A = 24 + 3(4A). Then divide both sides by two: A= 12 + 1.5(2A).
That's how I would do it.
2006-11-10 17:47:02
·
answer #5
·
answered by Annie 4
·
1⤊
1⤋
2A/3 = 8 + 4A multiply x3 on both sides
2A = 3(8+4A) distribute the 3 into the parenthesis
2A=24+12A substract 12A on both sides
2A -12A = 24 simplify the left side
-10A = 24 divide by -10
A = -24/10 =-2.4
2006-11-10 17:47:50
·
answer #6
·
answered by kihela 3
·
7⤊
0⤋
2A/3 = 8 + 4A
A = (8+4A) X 3/2
a = -2
2006-11-10 18:08:48
·
answer #7
·
answered by Melody 2
·
0⤊
2⤋
-12/5, and i solved that in my head
2006-11-10 17:45:10
·
answer #8
·
answered by 120 IQ 4
·
0⤊
4⤋
um, 3.
2006-11-10 17:50:40
·
answer #9
·
answered by crystald 4
·
0⤊
2⤋
no
2006-11-10 17:45:13
·
answer #10
·
answered by Al Bundy 4
·
0⤊
3⤋